Polifuncionalidad y competitividad laboral bajo la metodología de la Gestión por Competencias en Corporación Médica San Martin S.A.C. en el periodo comprendido del año 2014 al primer semestre del año 2015 - Gámez Marreros, Astrid Carolina (2015)
The following research is to determine how much multi-functionality influences, as a strategy in human resources management, in competitiveness of the internal customers of “Corporación Médica San Martín S.A.C.” (CORPOMEDIC S.A.C). The research not only determines this relationship but also describes each variable. Correlational design was used character - causal longitudinal type, since data collection was performed in two periods (2014 and first semester of 2015), for which an inductive study was developed based on the answers of internal customers of CORPOMEDIC SAC in relation to the level of multi-functionality and degree of labor competitiveness. In spite of the new trends related to human resources management as options that lead to business success; they do not show the expected results; especially, when the most adequate strategy has not been analyzed according to the company´s features; and even if the right one has been identified but the procedure is not the correct one. Primarily, multi-functionality searches for improving working competitiveness of the internal customers; and it has being used in different countries in Latin America such as Chile, Ecuador and El Salvador Republic. During the following research the concerned company has found a difficult process that implies a migration from the traditional proposal which took place many years ago. The main factor that limited the meaningful influence of the multi-functionality in working competitiveness, for this company, was the absence of an adequate implementation methodology, which allows generating during the process the capacity that each internal customer needs in order to contribute to the strategy, mission and vision